Pembuatan Aplikasi Validasi Document Tagihan Pembelian Barang Secara Digital Menggunakan OCR dengan tool tesseract pada System Portal Perusahaan - Septio, Pius Aldi; Prasetyo, Sri Yulianto Joko (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
This journal reviews the Making of a Digital Invoices Document Validation Application Using OCR with the tesseract tool on the Company Portal System. This study aims to implement Optical Character Recognition (OCR) using the tesseract tool in the company portal to make it easier to validate invoices. The method used is a prototype with the aim of building a system model where the system is based on user needs where the user does not provide input and output details. The results of the application that was made were tested using Black Box testing with the results that all application functions can be used properly.